Die Ned. Geref. Gemeente Stellenbosch-Noord, 1953-1970 : die beginjare - Claassen, Johannes Theodorus (Stellenbosch : Stellenbosch University, 2012)
Verhandeling (B. Th.) -- Universiteit van Stellenbosch, 1994.